COMPARISON OF MOTOR ABILITIES WITH FEMALE STUDENTS, DEALING WITH ATHLETES AND NON ATHLETES - Vildane Jašari; Abedin Ibrahimi; Kostovska Vesela; Branimir Mikić; Žarko Kostovski (Sport Scientific And Practical Aspects, 2025)
The research was conducted on a sample of 170 female students at the age of 14-16 years, from the elementary school. According to the research criteria, answering the question of the requirement for engaging in sports, the sample was divided on two subsamples, and with this research 170 girls were tested, from which 70 were defined as female students who regularly attend classes of physical education and are dealing with volleyball and 100 were defined as female students who regularly attend classes of physical education but are not dealing with any sport. The main goal of this research is partially establishing the quantitative and structural differences in basic-motor abilities of female students at the age of 14-16 years dealing with sports (volleyball) and non athletes. For the determination of the partial quantitate differences on uni variant level between the two subsamples t-test for small independent samples was applied. Based on the results of Wilk’s Lambda, and in association with Rao’s approximation, are giving a significant difference Q = .00 (p- level = 0.00) of the analyzed space. From the analysis of the results it can be concluded that there are differences between groups in the examined space. By applying the uni variant analysis of variance (ANOVA), can be seen statistically significant difference between respondents in the two groups of respondents in the variables: From the results of the t-test, it can be concluded that the analyzed group of respondents statistically significant differs in the variables.